Remote operation of cross-sectional imaging devices as a new form of teleoperation: Structural, technical, regulatory, and qualification aspects in Germany - Deistung, Andreas; Gussew, Alexander; Schneider, Jens; Beblacz, Alexander; Pech, Maciej; Wohlgemuth, Walter A. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2024)
Background There is a significant shortage of radiographers in Germany and this shortage is expected to increase. Thus, it is becoming increasingly difficult for radiological facilities to adequately provide their services for the required period of time. Teleradiology has already been established for electronic transmission of diagnostic radiographic imaging examinations between two geographical locations for diagnostic reporting. Recently, the concept of teleoperating radiological devices has become increasingly attractive.Method We examined the potential of teleoperating magnetic resonance imaging (MRI) in radiological facilities within the German regulatory framework in order to address the shortage of qualified personnel. To this end, we are introducing the concept of remote scanning, the structural foundations, the technical requirements associated with it, as well as the legal and educational qualifications of the relevant professional groups. Furthermore, suggestions regarding nomenclature and necessary standard operating procedures to efficiently integrate teleoperation into a clinical workflow adhering to high patient safety standards are provided.Results Companies provide technical solutions or even experienced radiographers as a service on demand for teleoperating radiological imaging devices remotely from a distance. There should be a comprehensive on-site strategy to effectively embed remote scanning into clinics. Local information technology and data security institutions should be involved in implementation. In order to guarantee that the remote operation workflow is able to provide health care services in line with regulative and legal standards, it is essential to implement standardized personal and institutional training, certifications, and accreditation procedures. Standard operating procedures (SOPs) and checklists for the involved staff, which are adapted to the local workflow in the participating facilities, are beneficial.Conclusion Remote MRI scanning is an evolving technology that further expands the concept of teleradiology to include teleoperations and provides flexibility with respect to the staffing of MRI operators. Careful consideration and dedicated expertise of all involved parties are required to ensure patient safety, meet regulations, and successfully integrate teleoperations into clinics.Key points Citation Format
Keywords: magnetic resonance imaging; computed tomography; remote scanning; teleworking; teleradiology; diagnostic radiology